2012
DOI: 10.1177/1948550611434400
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Weight of Weight Stigma

Abstract: The authors theorized that overweight individuals experience social identity threat in situations that activate concerns about weight stigma, causing them to experience increased stress and reduced self-control. To test these predictions, women who varied in body mass index (BMI) gave a speech on why they would make a good dating partner. Half thought they were videotaped (weight visible); the remainder thought they were audiotaped (weight not visible). As predicted, higher BMI was associated with increased bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
189
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(209 citation statements)
references
References 37 publications
8
189
1
4
Order By: Relevance
“…This study is novel as it extends previous studies of weight salience and eating (Major et al, 2012;McFerran et al, 2010aMcFerran et al, , 2010bShimizu et al, 2014) to examine food choices in the real world. We also tested whether subtle weight cues unrelated to eating, rather than live exposure to an overweight individual consuming food, can influence real-world eating.…”
Section: Tablementioning
confidence: 88%
See 1 more Smart Citation
“…This study is novel as it extends previous studies of weight salience and eating (Major et al, 2012;McFerran et al, 2010aMcFerran et al, , 2010bShimizu et al, 2014) to examine food choices in the real world. We also tested whether subtle weight cues unrelated to eating, rather than live exposure to an overweight individual consuming food, can influence real-world eating.…”
Section: Tablementioning
confidence: 88%
“…Considering previous evidence that weight salience affects high Body Mass Index (BMI) individuals more than low BMI individuals (Major, Eliezer, & Rieck, 2012), we hypothesized that any observed effects would be strongest in overweight and obese participants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, others have characterized weight stigma as a potential stressor (Brewis & Wutich, 2012;Major, Eliezer, & Rieck, 2012;Muennig, 2008). Major et al (2012) tested this idea experimentally in a recent study by exposing individuals to a potentially weight-stigmatizing task. They found that high BMI women in the weight-stigmatizing condition had increased stress perceptions and blood pressure compared to a condition in which weight was not salient.…”
Section: Step 1 Weight Stigma As a Psychological Stressormentioning
confidence: 99%
“…Being the target of discrimination, at least in domains such as racial discrimination, can disrupt self-regulation attempts through depleting the well of self-regulation, known as ego depletion (Inzlicht et al, 2006). Major et al (2012) found that women high in BMI had decreased executive control compared to those not exposed to weight stigma, and Major, Hunger, Bunyan, and Miller (2014) found that participants exposed to weight stigma reported less dieting self-efficacy than those in the control condition. These studies together provide a foundation of evidence indicating that increased eating behavior may be one response to experiencing weight stigma.…”
Section: Eating Behavior Mechanismsmentioning
confidence: 99%
“…El estigma de obesidad genera comportamientos que no contribuyen al control del peso 29 , tales como el retraso o evitación en la búsqueda de prestaciones médicas 30,31 , menor motivación por realizar actividad física 32,33 o una ingesta calórica superior a la recomendada por los especialistas 19,34,35 . Además, la discriminación derivada del estigma, se ha asociado a presión arterial elevada, lo que pone en un doble riesgo a los obesos 28,36,37 .…”
Section: Consecuencias Del Estigma De Obesidad En Las Víctimasunclassified